Monitoring the impact of COVID-19 in Myanmar: Rice millers - August 2020 survey round - Goeb, Joseph; Zone, Phoo Pye; Tang, Yulu (International Food Policy Research Institute, 2020)
This is the second policy note in a series presenting the results from telephone surveys with approximately 400 rice millers in three important rice-growing regions of Myanmar: Ayeyarwady, Bago, and Yangon. Mills are the most important link between farms and consumers in the rice value chain. In addition to drying, milling, processing, and storing rice, mills also buy paddy directly from farmers and often provide farmers with inputs on credit. Thus, any shocks to rice mills will impact both rural rice-producing households and urban consumers. To understand how the COVID-19 crisis and the corresponding policy responses are affecting the business activities of rice mills in Myanmar, we are conducting a panel telephone survey with rice millers. Interviews have been conducted every 30 days starting in July 2020, continuing through the monsoon harvests and ending in November. This report presents the results from the second survey round conducted in August. Interviews were completed by August 22, before a second wave of COVID-19 infections began to spread widely in Myanmar.